Gill’s model of the Antarctic Circumpolar Current, revisited: The role of latitudinal variations in wind stress - Marshall, D; Munday, D; Allison, L; Hay, R; Johnson, H (Elsevier, 2015)
Gill’s (1968) model of the Antarctic Circumpolar Current (ACC) is reinterpreted for a stratified, reduced-gravity ocean, where the barotropic streamfunction is replaced by the pycnocline depth, and the bottom drag coefficient by the Gent and McWilliams eddy diffusivity. The resultant model gives a simple description of the lateral structure of the ACC that is consistent with contemporary descriptions of ACC dynamics. The model is used to investigate and interpret the sensitivity of the ACC to the latitudinal profile of the surface wind stress. A substantial ACC remains when the wind jet is shifted north of the model Drake Passage, even by several thousand kilometers. The integral of the wind stress over the circumpolar streamlines is found to be a useful predictor of the magnitude of the volume transport through the model Drake Passage, although it is necessary to correct for basin-wide zonal pressure gradients in order to obtain good quantitative agreement.